Respiration kinetic of mango (Mangifera indica L.) as function of storage temperature (2016)
ABSTRACT: Respiration of cut mango (Mangifera Indica L.) cv. Tommy Atkins was studied using the closed system method at three temperatures (4, 20 and 35 °C). Two models were used to estimate the gas concentration, which were adjusted through non-lineal regression algorisms using Matlab R2011a software. Three mathematic models, a model based on Michaelis-Menten’s enzymatic kinetics, and two models based on regression analysis, in one of which a saturation equation was included as a new proposal in this field, were set to predict the substrate respiration rate. Results made evident the positive effect of temperature on mango respiration rate. The model with the best adjustment to mango respiration rate was Michaelis-Menten’s with an adjusted correlation coefficient of 0.9811 and 0.9747 for CO2 and O2 respectively, with a relative mean error lower than 10%.